Micropropagation of Drosophyllum lusitanicum (Dewy pine), an endangered West Mediterranean endemic insectivorous plant - Gonçalves, Sandra (2013)
In this work, in vitro clonal propagation of Drosophyllum lusitanicum (Dewy pine) was obtained from seedlings germinated in vitro. Seeds were collected in various populations identified in the Algarve region and germinated in vitro on MS medium supplemented with 0.5 mg l 1 BA (6-benzyladenine) and 0.1 mg l 1 GA3 (gibberellic acid). The obtained shoots were used in several multiplication assays. The best results were observed in MS medium supplemented with 0.2 or 0.5 mg l 1 zeatin. The highest rooting frequency (83%) was observed on 1/4MS medium supplemented with 0.2 mg l 1 IBA (indole-3-butyric acid). Fifty percent of the plantlets were successfully acclimatized to ex vitro conditions, exhibiting normal development. Plans are underway to reintroduce the in vitro produced plants from this study in selected locations in their natural habitat.